Exploring Factors Contributing to Trust in the Russian Government: An Analysis of Pro-Kremlin Twitter Accounts - Giantzaklidis, Niko (2024)
In the months leading up to Russia's full scale invasion of Ukraine, the Russian government launched an information operation belittling or even mocking claims of an imminent invasion. Despite the transparent deception, many Twitter users appeared to be supportive of the Russian government shortly after the launch of the invasion. This thesis aims to identify factors that could contribute to persisting trust in official Russian communication channels by analyzing public user data of over 27 000 Twitter accounts that kept engaging positively with official Russian communication channels.